Implementation of the new student admission policy or Penerimaan Peserta Didik Baru (PPDB) through the zoning system at SD Inpres Perumnas - Kalsum, Amanda; Nur'Iva, Muhammad Irvan; Herman, Herman; Rahayu, Rahayu (Priviet Social Sciences Journal, 2026)
This study aims to analyze the implementation of the New Student Admission (PPDB) policy through the zoning system at SD Inpres Perumnas Makassar City using the George C. Edwards III model which includes communication, resources, disposition, and bureaucratic structure. The research uses a qualitative approach with a descriptive case study design. Data was obtained through interviews, observations, and documentation of five informants, namely the principal, operator, PPDB committee, and two parents of students. At SD Inpres Perumnas, communication is carried out in a structured and multi-channel manner, including official circulars, coordination meetings, online groups, banners, and helpdesk posts. At SD Inpres Perumnas, communication is carried out in a structured and multi-channel manner, including official circulars, coordination meetings, online groups, banners, and helpdesk posts. The school prepares competent committees and operators, adequate technological facilities, and document support from students’ parents. The school prepares competent committees and operators, adequate technological facilities, and document support from students' parents. Attitude and commitment, school principals and teachers show high commitment in carrying out the technical instructions of the Education Office, while parents of students tend to accept and understand the objectives of the policy. A clear and organized bureaucratic structure facilitates effective policy implementation. A firm division of tasks, continuous coordination, and responsiveness to students' parents ensure that the registration process takes place in an orderly, directed, and transparent manner. The implementation of the PPDB zoning system still faces technical, administrative, and public perception challenges, including network disruptions, system access during a surge in registrants, dismatches in population data, and parents' understanding of the registration flow. This challenge shows that even though policies have been implemented in accordance with regulations, improvements in technical aspects, services, and socialization are still needed.